Effect of Annealing Treatment on Sensing Response of Inorganic Film Taste Sensor to Sweet Substances - Tomoki Shinta; Hidekazu Uchida; Yuki Hasegawa (Sensors)
The effect of annealing treatment on an inorganic film for taste sensors has not been fully elucidated. In this study, we developed an inorganic film taste sensor using SnO2 as a sensitive film and evaluated the effect of annealing treatment on its sensing response to sweet substances. First, we confirmed from XRD patterns that annealing at 600 °C caused a change in crystal orientation. Next, the taste sensor response to acesulfame potassium solution, which is a high-intensity sweetener and an electrolyte, showed a negative response with high concentration dependence. On the other hand, the sensors exhibited a positive response to non-electrolytes such as aspartame and glucose, with the sensor annealed at 600 °C showing a larger response to non-electrolytes compared to the other sensors. In terms of concentration dependence, the response to aspartame was higher, whereas the response to glucose was lower. Also, a reduction in variability was observed after annealing treatment at 150 °C and 300 °C. This phenomenon was clarified by comprehensively investigating various properties.